O uso da robótica educativa e o desenvolvimento de competências e habilidades matemáticas - Almeida Neto, Carlos Alves de (2014)
This work is the result of two experiments in educational area. The first Professor of Mathematics from 2010 to 1013, at the Municipal School José Ramos Torres de Melo, in Fortaleza / CE, the classes from 6th to 9th grade of elementary 2 Teaching, using as a pedagogical tool in some of my classes at Educational Robotics where the mathematical contents seen in the classroom were used in practice, in assemblies and programming of robots. The second experience was as Contributor of the National Institute of Studies and Research Teixeira ( INEP ) , from 2010 to the present day , acting as winemaker and Chartered Items for composition of Large Scale Reviews that make up the System of Basic Education Reviews - Saeb, such as the National High School Exam ( ESMS ), Brazil proof that is applied in Brazilian public schools in the 5th and 9th grades of elementary school and 3rd year of high school and finally the National Certification Examination for skills for Youth and Adults ( ENCCEJA ) facing Brazilian Youth and Adults who have not had the opportunity to complete basic education at the right age, both in Brazil and in other countries. All these imaging techniques are formulated and based on a statistical model called Item Response Theory (IRT) whose items (questions) are constructed according to a matrix based reference Skills and Abilities. Each of these tests has its own matrix composed of descriptors. For example, the Matrix Model for the 9th year of elementary school, currently has 37 descriptors, divided into 4 fields of knowledge, called themes, namely, Theme I - Space and Shape, Theme II - Quantities and Measurements, Theme III - Numbers and Operations / Algebra and Functions and Theme IV - Treatment Information. Overall, each of these matrices assess the skills and abilities that students should have acquired by the end of each cycle, ie, a student of 9th class will be inferred about the Skills and Abilities that should have been developed during the course of 4 years that make up the elementary school 2 . This paper attempts to show that the use of robotics as a tool for learning, helps students to develop skills and abilities contained in these reference matrices as well as others that are important to the young and future citizen of the twenty-first century, both in the world of work, as in their personal relationships. For this we will make an analysis of assemblies of programming problems and situations that are put for some robots, for grades 6th to 9th grade, checking which skills and abilities are involved in carrying out these activities, thus making a parallel with the Mother gifts described in Reference 9 th year. Thus showing that the use of robotics in Mathematics assists and encourages the development of skills and math skills.